Improvement in Postural Control Following Concussion in Adolescent Athletes: From Clinical Presentation to Initiation of Return to Play. Issue 5 (31st May 2022) - Erdman, Ashley L.; Ulman, Sophia; Loewen, Alex; Worrall, Hannah; Tulchin-Francis, Kirsten; Jones, Jacob C.; Chung, Jane S.; Ellis, Henry B.; Cullum, C. Munro; Miller, Shane M.
Background: Impairments in balance or postural control are common following sport-related concussion (SRC). The Balance Error Scoring System (BESS) is widely utilized to assess static postural stability, but laboratory-based balance measures have been shown to more accurately detect changes in postural control. Hypothesis/Purpose: To determine whether postural control improved between presentation to the sports medicine clinic and return-to-sport (RTS) initiation, and whether this trend mirrored symptom scores and cognitive performance. A secondary aim was to assess whether changes in postural control were more accurately captured with center of pressure (COP) based measures compared to BESS. Methods: Patients diagnosed with a SRC were tested within 10 days of presentation (V0) and when cleared by a physician to begin a RTS protocol (V1). Clinical measures included Immediate Post-Concussion Assessment and Cognitive Testing (ImPACT) and the King-Devick (K-D) test. The BESS was performed with eyes closed while standing barefoot on a force platform for 6 conditions: double-limb stance, single-limb stance, and tandem stance on both firm and foam surfaces. BESS scores and total balance time were recorded for each condition, and COP-based measures were computed for both double-limb stance conditions (Table 1). Sample entropy was computed to quantify COP regularity over time with increased values indicating improvement in postural control. Wilcoxon signed-rank tests were performed to determine significance between visits ( α <0.05). Results: Forty patients (17 males, 13.8±2.0 years) were included for analysis. ImPACT verbal and visual memory scores improved by 10% and 12%, respectively, total symptom score decreased (V0 18.03±13.85, V1 0.97±2.08; p <0.01), and visual motor speed and reaction time were both 11% faster on the K-D test. For postural control, the BESS indicated significant improvement given the reduction in errors on both surfaces (Firm Total: V0 3.23±2.09, V1 2.25±2.11, p =0.01; Foam Total: V0 7.38±2.05, V1 6.08±1.76, p <0.01; Table 1). Similarly, COP-based measures exhibited better overall balance between visits (Figure 1), primarily in the medial-lateral direction on the firm and the anterior-posterior direction on the foam. Lastly, sample entropy improved between visits, indicating more effective postural control. Conclusion: Significant improvement in postural control was observed during the recovery period which mirrored improvement in symptom scores and cognitive performance. Additionally, while COP-based measures showed similar trends to the BESS, they provided more detailed information in regards to balance recovery. Specifically, findings from the double stance condition highlight the utility of a more advanced assessment of postural control for determining RTS readiness following a SRC. Table 1. COP-based measures of balance performance at diagnosis (V0) and clearance (V1) visits Figure 1. Representative stabilograms of double stance balance on firm and foam surfaces at diagnosis (V0) and clearance visits (V1)